GOD SERVANTS' KNOWLEDGE AND STIGMA OF TUBERCULOSIS IN KUPANG INDONESIA - Imelda Februati Ester Manurung; Luh Putu Ruliati; Helga J. N Ndun; Aminah H Baun; Yumiati Ke Lele; Chatarina U Wahyuni (Public Health of Indonesia)
Background: Knowledge and stigma are the factors that determine the success of TB control. The people of East Nusa Tenggara still rely heavily on the support of God's servants in addressing health issues. God's servant is someone who is believed to have the gift of healing through prayer to the Lord Jesus.